Children's Beliefs About Possibility Differ Across Dreams, Stories, and Reality. Issue 6 (27th July 2020) - Goulding, Brandon W.; Friedman, Ori
Abstract : Are children's judgments about what can happen in dreams and stories constrained by their beliefs about reality? This question was explored across three experiments, in which four hundred and sixty‐nine 4‐ to 7‐year‐olds judged whether improbable and impossible events could occur in a dream, a story, or reality. In Experiment 1, children judged events more possible in dreams than in reality. In Experiment 2, children also judged events more possible in dreams than in stories. Both experiments also suggested that children's beliefs about reality constrain their judgments about dreams and stories. Finally, in Experiment 3 children were asked about impossible events more typical of dreams and stories. In contrast with the other experiments, children now affirmed the events could happen in these worlds.